INTERNATIONAL RELATION ISSUES AND VISION OF INDIA IN INDO-PACIFIC - Tran Nam Tien (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
In recent years, Indo-Pacific Region has experienced new vision and international relation issues of India, a big country in Asia region. This is new concept starting from Shinzo Abe in Japan and later, Donald Trump in USA. China and India has 2 big countries in Asia and has shown strength and high competitiveness in Asia region. By using qualitative, synthesis, historical and dialectical materialism methods, this papers aims to figure out vision and international relation issues of India, a big country in IndoPacific context.